Characterization of the far-red fluorescent probe MitoView 633 for dynamic mitochondrial membrane potential measurement - Ernst, Patrick; Kim, Seulhee; Yang, Zengqiao; Liu, Xiaoguang Margaret; Zhou, Lufang (Frontiers in Physiology, 2023)
Introduction: MitoView 633, a far-red fluorescent dye, exhibits the ability to accumulate within mitochondria in a membrane potential-dependent manner, as described by the Nernst equation. This characteristic renders it a promising candidate for bioenergetics studies, particularly as a robust indicator of mitochondrial membrane potential (DYm). Despite its great potential, its utility in live cell imaging has not been well characterized. Methods: This study seeks to characterize the spectral properties of MitoView 633 in live cells and evaluate its mitochondrial staining, resistance to photobleaching, and dynamics during DYm depolarization. The co-staining and imaging of MitoView 633 with other fluorophores such as MitoSOX Red and Fluo-4 AM were also examined in cardiomyocytes using confocal microscopy. Results and Discussion: Spectrum analysis showed that MitoView 633 emission could be detected at 660 ± 50 nm, and exhibited superior thermal stability compared to tetramethylrhodamine methyl ester (TMRM), a commonly used DYm indicator, which emits at 605 ± 25 nm. Confocal imaging unequivocally illustrated MitoView 633’s specific localization within the mitochondrial matrix, corroborated by its colocalization with MitoTracker Green, a well-established mitochondrial marker. Furthermore, our investigation revealed that MitoView 633 exhibited minimal photobleaching at the recommended in vitro concentrations. Additionally, the dynamics of MitoView 633 fluoresce during carbonyl cyanide-p-trifluoromethoxyphenylhydrazone (FCCP, a mitochondrial uncoupler)-induced DYm depolarization mirrored that of TMRM. Importantly, MitoView 633 demonstrated compatibility with co-staining alongside MitoSOX Red and Fluo-4 AM, enabling concurrent monitoring of DYm, mitochondrial ROS, and cytosolic Ca2+ in intact cells. Conclusion: These findings collectively underscore MitoView 633 as a superb molecular probe for the singular or combined assessment of DYm and other indicators in live cell imaging applications.